STAGE FEAR AS A COMMUNICATIVE BARRIER IN THE CLASSROOM IN THE BUSINESS ENGINEERING CAREER OF THE PRIVATE UNIVERSITY OF THE EAST SUBSIDIARY CIUDAD DEL ESTE - Vanessa Ruiz Diaz de Salvioni, Viviana; Armoa, Alcides (Revista Gênero e Interdisciplinaridade, 2023)
Stage fright, also known as stage fright or fear of public speaking, is a recognized phenomenon that affects many people in different contexts. This research focuses on analyzing how stage fright becomes a communication barrier in the educational field, specifically in the classroom. The methodology used is mixed research under the Quantitative and Qualitative approach, data collection was carried out through interviews and survey. The results indicate that stage fright has a significant impact on students’ communication in the classroom. Those who experience stage fright tend to avoid actively participating in discussions, oral presentations, and other activities that require speaking in front of their peers. This negatively affects their learning by missing opportunities to express ideas, ask questions and participate in discussions. Factors that contribute to stage fright in the educational context are identified, such as fear of judgment and negative evaluation, lack of confidence in communication skills, and peer pressure. These factors create anxiety and stress, further hindering students’ ability to communicate effectively. As a result of the research, strategies are proposed to address stage fright and promote effective communication in the classroom. These include relaxation techniques and stress management, creating a supportive and trusting environment, designing activities that promote active participation by all students, and training teachers in managing stage fright.